Proteomic study and flux analysis of metabolic pathways of halophilic microorganisms - Ceylan, Selim (My University, 2010)
HALOFİLİK MİKROORGANİZMALARIN METABOLİK YOLLARININ PROTEOMİK ÇALIŞMASI VE AKI ANALİZİ Bu çalışmada Ege Bölgesi, İzmir Çamaltı Tuzlasından izole edilen ve Halomonas sp. AAD12 olarak isimlendirilen gram negatif ılımlı halofilik bakterinin çeşitli stres koşullarına verdiği proteomik cevaplar incelenmiştir. 16S rDNA gen dizi analizleri sonucunda AAD12’ nin, Halomonas soyundan olan Halomonas halophila’ ya %99 benzerlik gösterdiği belirlenmiştir. Halomonas sp. AAD12 bakterisinin yüksek tuz konsantrasyonu, düşük sıcaklık, fenol ve oksijen azlığı gibi farklı stres koşullarına adaptasyonu proteom teknolojisi araçları kullanılarak incelenmiştir. Proteom analizleri iki boyutlu jel elektroforez ile gerçekleştirmiştir. Optimum ve stres şartlarındaki proteom haritaları karşılaştırılarak stres şartlarında ekspresyonu artan ya da azalan proteinler belirlenmiştir. Matrix-assisted laser desorption ionization time of flight kütle spektrometrisi (MALDI-TOF) farklı miktarlarda sentezlenen proteinleri tanılayarak bakteride gerçekleşen bu adaptasyon tepkilerinin anlaşılmasında kullanılmıştır. Stres şartlarına adaptasyon sürecinde değişikliğe uğrayan çok sayıda protein, AAD12 nin çevresel değişiklikler karşısında gen ekspresyonunu değiştirdiğini göstermektedir. Proteomik ve fizyolojik çalışmalar, AAD12 metabolizmasının stres şartlarında direnç kazanırken ya da büyürken etkili bir şekilde yeniden organize edildiğini göstermiştir. Tanımlanan proteinlerin, protein ve nükleik asit sentezinin korunmasında, taşınımda ve oksidatif stres metabolizmalarında hayati önem taşıdıkları belirlenmiştir. Bu çalışma ılımlı halofilik bakterilerin oksijen azlığı ve fenole adaptasyon mekanizmalarının proteomik analiz teknikleri kullanılarak incelendiği ilk çalışmadır. Ayrıca bu çalışmada AAD12’ nin tuzlu atık sulardan fenol uzaklaştırılması için önemli olan fenolün biyo-bozunumu kabiliyetine de sahip olduğu belirlenmiştir.

PROTEOMIC STUDY AND FLUX ANALYSIS OF METABOLIC PATHWAYS OF HALOPHILIC MICROORGANISMS In this study, proteomic response of a gram-negative, moderately halophilic bacterium, designated as strain AAD12 isolated from Çamaltı Saltern Area, located in Aegean Region of Turkey to various stres conditions was investigated. Strain AAD12 belongs to the genus Halomonas, with an identitiy of 99.0% to Halomonas halophila based on the 16S rDNA gene sequence. The adaptation ability of Halomonas sp. AAD12 to various stress conditions such as high salinity, low temperature, phenol, and oxygen limitation was studied using proteomics tools. Proteome analysis carried out by means of two-dimensional polyacrylamide gel electrophoresis. Comparative analysis of the proteome profiles of strain AAD12 grown normal and stress conditions allowed us to identify up-regulated and down-regulated proteins under stress conditions. Matrix-assisted laser desorption ionization time of flight (MALDI) mass spectrometry was used to identify differentially expressed proteins for understanding adaptive responses within the bacterium. The impressive number of proteins that displayed changes in their relative rates of synthesis during the adaptation to stress conditions conveys the idea that strain AAD12 is an organism in which gene expression varies in response to environmental changes. The proteomic and physiological data presented in this study reveal that stress conditions induce a deep metabolic reorganization in strain AAD12 either during the process of acquisition of resistance or during growth in stress conditions. The identified proteins included those that play vital roles for maintenance such as protein and nucleic acid synthesis, transport and oxidative stress. This is so far the first study on oxygen limitation and phenol adaptation of moderately halophilic bacteria using proteomic tools. Phenol degradation ability of the strain was also determined which is promising for degradation of phenolic substances in saline wastewaters.
Keywords: Kimya Mühendisliği; Mikroorganizmalar